Jews in Prekmurje Literature: The Case of Jožef Smej and Miško Kranjec - Marija Stanonik (Edinost in Dialog, 2021)
Thanks to the former Hungarian laws, Prekmurje is the region of Slovenia where a fairly compact Jewish community has been preserved for the longest time. The article focuses on the comparative analysis of the Jews in the literature of two main personalities of Prekmurje literature. They differ already in the naming of the people who are the subject of the discussion here. The first adresses Jews as »Židi«, the second as »Judi«. We researched what else separates them in literature and what might connect them. Miško Kranjec evolved from his originally Christian habitus and became a distinctly socially engaged writer, which also marked his attitude towards the Jews, whom his literary figures perceive as members of the exploitative class. As a Catholic priest, Jožef Smej is committed to the Gospel mission, to which also the Second Vatican Council dictates a dialogical stance towards related religions. The Jews in his literature are deeply religious and tragic figures.